2019
DOI: 10.4012/dmj.2018-140
|View full text |Cite
|
Sign up to set email alerts
|

Wear of dental materials: Clinical significance and laboratory wear simulation methods —A review

Abstract: This review focusses on tribological aspects of teeth during function, the clinical significance of wear, wear of natural teeth and restorative materials and laboratory methods to simulate wear of restorative materials. Ceramic, metal alloy and amalgam show low material wear, whereas resin-based materials demonstrate substantial wear in the long term. The clinical wear shows a high variability with the patient factor accounts for about 50% of the variability. Wear as such seldomly compromises the function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 99 publications
1
58
1
2
Order By: Relevance
“…The connection and correlation of these parameters are explained excellent by DeLong et al [29]. However, the methodology of wear measurements under clinical conditions is currently intensively discussed [30][31][32][33][34]. In this clinical study, the parameter of vertical height loss measured perpendicular to working surface was applied.…”
Section: Discussionmentioning
confidence: 97%
“…The connection and correlation of these parameters are explained excellent by DeLong et al [29]. However, the methodology of wear measurements under clinical conditions is currently intensively discussed [30][31][32][33][34]. In this clinical study, the parameter of vertical height loss measured perpendicular to working surface was applied.…”
Section: Discussionmentioning
confidence: 97%
“…Wear of composite resins is mainly influenced by filler characteristics that determine the Sa and friction coefficient. Besides the filler load, shape, and hardness of filler particles, the quality of their bond to the organic matrix and the density of the polymer network determine their wear resistance [ 48 ]. The present study tested three-body abrasion by toothbrushing and determined that TEC was the material with the highest Sa, although significant differences before and after wear were found for all the materials.…”
Section: Discussionmentioning
confidence: 99%
“…The high Sa of TEC could be attributed to large pre-polymerised fillers that bonded poorly to the resin matrix, thus allowing their easy dislodgement. The low FM of SDR and FBF probably gave them an advantage with regard to Sa, making them more pliable [ 48 ]. Interestingly, St values determining the peak-to-valley height were significantly higher after wear for TEC and FBF, but not for SDR.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusal wear of the resin-based CAD/CAM restorations was observed at a relatively high rate in the posterior area [5,9]. It is known that clinical wear of resin-based materials is higher compared with ceramic materials and dental alloys [19]. However, the clinical wear of the resin-based restorations does not directly interfere with the clinical long-term results of the restorations [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that clinical wear of resin-based materials is higher compared with ceramic materials and dental alloys [19]. However, the clinical wear of the resin-based restorations does not directly interfere with the clinical long-term results of the restorations [19]. A review article suggested that recent resin-based materials, such as dispersed nanoparticle-filled composite resin and resin infused ceramic hybrid, have lower wear values than hybrid composite resin materials [20].…”
Section: Discussionmentioning
confidence: 99%